2005
DOI: 10.1007/s10238-005-0070-7
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against bactericidal/permeability–increasing protein (BPI–ANCA) in cystic fibrosis patients treated with azithromycin

Abstract: Autoantibodies against bactericidal/permeability-increasing protein (BPI-ANCA) were found in patients with cystic fibrosis (CF). It is speculated that they represent a marker of the chronic endobronchial infection and sustained inflammatory response in CF. Our aim was to evaluate whether azithromycin (AZM), through its antiinflammatory effect, could affect the level of BPI-ANCA in CF patients. Eighteen patients with CF aged 5.5-36.3 years (median 15.1) were enrolled in a randomised, double-blind, placebo-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…Other antigens that are sources of autoantibodies recognized by immunofluorescence ANCA assay include azurocidin, which appears to be related to ANCA secondary to drugs [185], lactoferrin [185], and so forth. Anti-BPI ANCA is detected with a high frequency in patients with cystic fibrosis and infections with Pseudomonas species [5356] and those with inflammatory bowel disease or primary sclerosing cholangiitis and presumed infections from enteric Gram-negative bacteria [186]. Anti-BPI ANCA increases the severity of both pulmonary and gastrointestinal infections through reductions of the clearance of bacteria and endotoxin by the leucocytes and, probably, through other nonspecific effects on immune complexes [187].…”
Section: Role Of Infections In the Pathogenesis Of Anca-mediated Dmentioning
confidence: 99%
“…Other antigens that are sources of autoantibodies recognized by immunofluorescence ANCA assay include azurocidin, which appears to be related to ANCA secondary to drugs [185], lactoferrin [185], and so forth. Anti-BPI ANCA is detected with a high frequency in patients with cystic fibrosis and infections with Pseudomonas species [5356] and those with inflammatory bowel disease or primary sclerosing cholangiitis and presumed infections from enteric Gram-negative bacteria [186]. Anti-BPI ANCA increases the severity of both pulmonary and gastrointestinal infections through reductions of the clearance of bacteria and endotoxin by the leucocytes and, probably, through other nonspecific effects on immune complexes [187].…”
Section: Role Of Infections In the Pathogenesis Of Anca-mediated Dmentioning
confidence: 99%
“…Zhao et al have shown BPI to be one of the major ANCA antigens in CF patients. 72 The presence of both IgA and IgG anti-BPI auto-Abs have been correlated to the severity of lung disease associated with CF. 71 Both the isotypes against BPI were directed toward its carboxy terminal domain, which is important for opsonization.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…The membrane-bound virulence factor lipopolysaccharide (LPS), expressed by all Gram-negative bacteria like P. aeruginosa, elicits an immunoglobulin M (IgM)-mediated antibody response that takes several days to fully develop, and this delay may increase the risk of death in severe infections [18]. Human monoclonal antibodies directed against P. aeruginosa LPS have demonstrated protection in various settings [19][20][21].…”
Section: Introductionmentioning
confidence: 99%